2017
DOI: 10.1002/aic.16042
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell biomanufacturing under uncertainty: A case study in optimizing red blood cell production

Abstract: As breakthrough cellular therapy discoveries are translated into reliable, commercializable applications, effective stem cell biomanufacturing requires systematically developing and optimizing bioprocess design and operation. This article proposes a rigorous computational framework for stem cell biomanufacturing under uncertainty. Our mathematical tool kit incorporates: high‐fidelity modeling, single variate and multivariate sensitivity analysis, global topological superstructure optimization, and robust optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…We could create a single-objective optimisation problem by setting a monetary value on the neotissue produced in the bioreactor, and optimise the design variables by maximising the difference between the monetary reward of the neotissue and the production cost, e.g. as in growing red blood cells [35], [36]. This would be equivalent to scalarisation, which is described later in this section.…”
Section: A Objective Functions: Tissue Engineering Applicationmentioning
confidence: 99%
“…We could create a single-objective optimisation problem by setting a monetary value on the neotissue produced in the bioreactor, and optimise the design variables by maximising the difference between the monetary reward of the neotissue and the production cost, e.g. as in growing red blood cells [35], [36]. This would be equivalent to scalarisation, which is described later in this section.…”
Section: A Objective Functions: Tissue Engineering Applicationmentioning
confidence: 99%
“…Although the HFs could only reach a 97% dead-end separation efficiency, the filtered suspensions contained a greater ratio of mononuclear to enucleated cells (5 : 1), more relevant to current hematopoietic culture than standard peripheral blood leukoreduction (1 : 1000), where higher MNC contents could lead to fouling. Of these leukoreduction methods, HF filters can be uniquely incorporated within long-term 3D cultures to filter nutrients and cells [ 19 , 20 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, such HEMA cultures inoculate rare CB CD34 + MNCs which are expanded at densities beneath 5 × 10 6 cells/mL. HEMA cultures require large medium volumes, abnormally high concentrations of expensive cytokines, and production costs 1-2 orders of magnitude above donated RBC unit costs [ 2 , 20 , 26 ]. A recently described immortalized erythroblast line could mitigate cell source limitations by providing unlimited RBC generation [ 42 ], while medium requirements and RBC harvest could be made more economically viable using proposed HFBR bioprocessing strategies, where CD235a enucleation rate would be a critical parameter for future study.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the prevalence of pre-existing intrinsic and extrinsic variability over external noise is important for developing key indicators to identify and predict the bioprocess variability. The phenomenon of "intrinsic disorder" has been widely studied in bioprocess conditions, and understanding and controlling the sources of variability are anticipated to play important roles in improving bioprocess control and optimization (Kim and Kino-oka, 2020b;Misener et al, 2018). Indeed, it has been shown that the phenotypic variability among stem cells can contribute to the inherent differences resulting from donor-dependent variability as well as changes induced during cellular reprogramming and expansion and cell handling processes such as passaging, freezing, or thawing (Kim and Kino-oka, 2018).…”
Section: Identifying Criteria and Indicators For Assessing External Forcing And Internal Variability-generated Uncertainly In Stem Cell Bmentioning
confidence: 99%